Hip hemiarthroplasty through the anterior based muscle sparing approach for femoral neck fractures: an operative technique - Cheong, Teddy; Kon Kam King, Charles; Moo, Ing How (Frontiers in Surgery, 2025)
Incidence of femoral neck fractures (FNF) in the elderly is rising. Hemiarthroplasty has long been regarded as the mainstay treatment for displaced FNFs in this population. The Anterior Based Muscle Sparing (ABMS) approach for hip arthroplasties is a relatively recent technique which utilises the intermuscular plane between the gluteus medius (GMed) and the tensor fascia lata (TFL) to gain access to the hip joint, thereby sparing the abductor muscles. Due to its proposed benefits of less post-operative pain, faster recovery and lower dislocation rates, it has increased in popularity in recent years. The approach also allows for the safe implantation of any femoral stem design and offers a relatively short learning curve. Given its muscle-sparing nature and favourable stability profile, the ABMS approach is an excellent option for managing displaced FNFs in the elderly population. There is limited literature on the surgical steps of the ABMS approach in hip hemiarthroplasties as treatment for geriatric FNFs. The ABMS approach can be performed in either supine or lateral decubitus position. This article gives a step-by-step description on how to perform a hip hemiarthroplasty using this technique in the lateral decubitus position. Intra-operative videos are provided to illustrate the key points of the surgery.